A Review on Enzymatic Response to Salt Stress and Genomic/Metagenomic Analysis of Adaptation Protein in Hypersaline Environment - Habeebat Adekilekun Oyewusi; Muhammad Muhammad; Roswanira Abdul Wahab; Fahrul Huyop (Journal of Tropical Life Science, 2021)
Microorganisms adapted to conditions of high salinity (low water activity) provide an understanding on how the problem of maintaining an efficient cell integrity under high osmotic stress conditions that had been tackled naturally. Almost all microbes adapting to extreme situations either by intracellularly amass inorganic ions (K+) to counterbalance high salt concentration or by synthesizing and accumulating certain organic solutes called compatible solutes that confer protection without affecting cell functions and this process may be chloride ion dependent in some microorganisms. However, the use of culture-independent method like genomic or metagenomics shields more light on the microbial diversity, gene structure and regulation as well as discovery of novel genes that led to understanding of their adaptation mechanism and roles in extreme environments. Therefore, microbes that survive this natural attenuation aimed at acclimatizing with the extreme environments could serve as the sources of biotechnologically essential molecules with an extensive array of uses.